2019
DOI: 10.1016/j.addr.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Self-emulsifying drug delivery system: Mucus permeation and innovative quantification technologies

Abstract: Mucus is a dynamic barrier which covers and protects the underlying mucosal epithelial membrane against bacteria and foreign particles. This protection mechanism extends to include therapeutic macromolecules and nanoparticles (NPs) through trapping of these particles. Mucus is not only a physical barrier that limiting particles movements based on their sizes but it selectively binds with particles through both hydrophilic and lipophilic interactions. Therefore, nano-carriers for mucosal delivery should be desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 166 publications
(195 reference statements)
0
38
0
1
Order By: Relevance
“…The presence of mucus is also important as it has been shown that SNEDDSs can rapidly permeate across this layer thanks to the low interaction of their hydrophobic surface with the hydrophilic regions of mucus and thanks to their low droplet size, consequently enabling higher drug absorption. 37,38 Thus, the inclusion of mucus on top of an in vitro permeation membrane is crucial to simulate the environment that SNEDDSs would be presented to in vivo, and allows these drug delivery systems to explicate the positive effect on drug absorption related to their high mucus permeation.…”
Section: In Vivo Absorption-in Vitro Permeation Correlationmentioning
confidence: 99%
“…The presence of mucus is also important as it has been shown that SNEDDSs can rapidly permeate across this layer thanks to the low interaction of their hydrophobic surface with the hydrophilic regions of mucus and thanks to their low droplet size, consequently enabling higher drug absorption. 37,38 Thus, the inclusion of mucus on top of an in vitro permeation membrane is crucial to simulate the environment that SNEDDSs would be presented to in vivo, and allows these drug delivery systems to explicate the positive effect on drug absorption related to their high mucus permeation.…”
Section: In Vivo Absorption-in Vitro Permeation Correlationmentioning
confidence: 99%
“…Despite several decades devoted to SEDDS development for various routes of administration, namely: oral, rectal, vaginal, ocular and nasal; the dermal route has remained relatively untouched [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The formidable barrier provided by the outermost skin layer can possibly be conquered by SEDDSs as these isotropic, thermodynamically stable mixtures, comprising oil, surface active agents and water, have the potential capacity to facilitate entry of drugs into underlying skin layers [ 24 , 25 ]. Modification of stratum corneum (SC) lipid arrangement can be achieved by natural oils included in topical SEDDSs [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…This explorative research aimed at developing topical clofazimine SEDDSs aiding in CTB as well as establishing criteria for these systems since SEDDSs provide simplified techniques suitable for industrial upscaling together with improved drug solubility [ 24 , 25 ] which has not yet been investigated for topical drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…However, other non‐interacting polymers such as poly(2‐alkyl‐2‐oxazolines) and poly(vinyl alcohol) have also been considered . Further examples include particles modified with zeta‐potential shifting polymers, as well as formulations equipped with mucolytic enzymes or thiol groups, self‐emulsifying drug delivery systems, and densely‐charged particles that have an overall neutral net charge (sometimes referred to as virus‐mimicking particles) . The latter concept is a nature‐inspired approach, where the aim is to mimic mucopenetrating viruses that have a high surface charge density but overall neutral net‐charge due to a balanced distribution of positive and negative charges, minimizing the affinity to mucus components and enables the viruses to cross the mucus almost unhindered …”
Section: Methodsmentioning
confidence: 99%